Game efficiency indicators of Olympic basketball performance - Milanovic, D.; Uzelac, N.; Sala, S. (Acta Kinesiologica, 2019)
The analysis of players' and teams' situational efficiency indicators is an important factor for planning and programming a training process, as well as the tactical preparationof top basketball teams. The purpose of this paper is to determine game related efficiency indicators i.e. parameters of competition performance in offence and defense phase of the basketball games for the outcome in 2016 Olympic male basketball. The sample used to conduct this research consisted of 30 opposing teams in 15 matches. Results showed that, on a global level, situational efficiency indicators influence final outcome of the basketball game by 97.5%. The most significant predictors of the final result of the match are the 2 points shot-unsuccessful, 3 points shot-unsuccessful, offensive and defensive rebounds, steals, and turnovers. These results can help coaches in preparing and controlling the training variables for high-level competitions.